2012
DOI: 10.18097/pbmc20125806702
|View full text |Cite
|
Sign up to set email alerts
|

The influence of inhibiting no formation on metabolic recovery of ischemic rat heart by apelin-12

Abstract: Apelin 12 (A-12) was synthesized by the automatic solid phase method with use of Fmoc 1H-NMR spectroscopy and mass spectrometry. Effects of apelin-12 (a peptide comprised of 12 aminoacids, A-12) on recovery of energy metabolism and cardiac function were studied in isolated working rat hearts perfused with Krebs buffer (KB) containing 11 mM glucose that were subjected to global ischemia and reperfusion. A short-term infusion of μM 140 A-12 in KB prior to ischemia enhanced myocardial ATP, the total adenine nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Intravenous administration of apelin-12 at a dose of 0.07 µmol/kg (0.1 mg/kg) reduced infarct size by 21%, at a dose of 0.35 µmol/kg (0.5 mg/kg) by 34% in reperfusion [ 34 ]. It was found that apelin-12 at a dose of 0.35 µmol/kg (0.5 mg/kg, intravenously) reduced infarct size by 40% in rats with reperfusion of the heart after CAO (40 min) [ 44 ]. Apelin-12 reduced infarct size by 33% at a dose of 0.7 µmol/kg (1 mg/kg).…”
Section: Cardiovascular Effects Of Apelinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intravenous administration of apelin-12 at a dose of 0.07 µmol/kg (0.1 mg/kg) reduced infarct size by 21%, at a dose of 0.35 µmol/kg (0.5 mg/kg) by 34% in reperfusion [ 34 ]. It was found that apelin-12 at a dose of 0.35 µmol/kg (0.5 mg/kg, intravenously) reduced infarct size by 40% in rats with reperfusion of the heart after CAO (40 min) [ 44 ]. Apelin-12 reduced infarct size by 33% at a dose of 0.7 µmol/kg (1 mg/kg).…”
Section: Cardiovascular Effects Of Apelinsmentioning
confidence: 99%
“…It was demonstrated that NO-synthase is involved in the cardioprotective effect of apelin-12 in the reperfusion of the heart both in vivo and in vitro [ 43 , 44 ]. Infusion of apelin-13 (0.5 µmol/L) protects isolated rat hearts against reperfusion injury [ 45 ].…”
Section: The Signaling Mechanism Of the Cardioprotective Effect Of Ap...mentioning
confidence: 99%
“…Furthermore, NO formation is involved in the process of recovery of energy metabolism induced by the apelin/APJ system. Restoration of energy metabolism increases functional recovery of the heart and decreases cell membrane damage in MIRI [147,148].…”
Section: Apelinmentioning
confidence: 99%